Strategic Location of Pokhara: The Perspective of Tourism - Khagendra Raj Poudel; Lal Bahadur Oli (Journal of Development and Administrative Studies, 2025)
Pokhara has emerged as one of Nepal’s most significant tourism destinations, with its development deeply rooted in historical milestones, strategic geography, and infrastructural growth. Since the 1950s, key events such as the first climb of Mt. Annapurna I by Maurice Herzog and the introduction of commercial trekking tourism by Colonel Jimmy Roberts have established Pokhara as a gateway to the Annapurna region. Its central location has further enhanced its role as a connecting hub for major tourism circuits like the Golden, Silver, and Adventure Triangles. Supported by contributions from notable national and international figures, Pokhara has grown to offer diverse tourism experiences ranging from nature and culture to adventure-based activities. Empirical data from 2020 indicates that Pokhara received 38.5% of Nepal’s international tourists, contributing 21.2% of tourism income and 17.5% of direct employment. Despite possessing 38.3% of the country’s accommodation capacity and 43.8% of tourist-standard hotels, tourist stays remain short, and daily expenditures relatively low. This underscores the need for targeted interventions to enhance visitor engagement, extend stay durations, and diversify tourism services. With strategic planning and sustainable development, Pokhara holds strong potential to further strengthen its position as a leading destination in Nepal’s tourism landscape.